2019
DOI: 10.2136/vzj2018.04.0083
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Matric Potential, Solid Interfacial Chemistry, and Wettability on Isotopic Equilibrium Fractionation

Abstract: Core Ideas Matric potential controls the equilibrium fractionation factor between soil water and water vapor. Surface chemistry determined by X‐ray spectroscopy affects the equilibrium fractionation factor. A conceptual isotope retention characteristic approach is presented. Soil water stable isotopes are widely used for geo‐ and ecohydrological applications. However, the signature of the soil water isotopic composition in the environment depends on various factors. While recent work has shown matric potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 78 publications
(122 reference statements)
5
31
0
Order By: Relevance
“…Therefore, the bulk soil water (added reference water) is partitioned into two parts: water in smaller pores with depleted isotopic composition and water in relatively large pores with enriched isotopic composition. Moreover, this effect increases with increasing soil matric suction (Gaj et al, ), which responds to increasing clay content at the same soil water content or decreasing water content for the same soil (Assouline et al, ). Furthermore, similar effect of clay and water contents on the measured δ 18 O was also reported by Oerter et al ().…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the bulk soil water (added reference water) is partitioned into two parts: water in smaller pores with depleted isotopic composition and water in relatively large pores with enriched isotopic composition. Moreover, this effect increases with increasing soil matric suction (Gaj et al, ), which responds to increasing clay content at the same soil water content or decreasing water content for the same soil (Assouline et al, ). Furthermore, similar effect of clay and water contents on the measured δ 18 O was also reported by Oerter et al ().…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, this effect increases with increasing soil matric suction (Gaj et al, 2019), which responds to increasing clay content at the same soil water content or decreasing water content for the same soil (Assouline et al, 1998). Furthermore, similar effect of clay and water contents on the measured δ 18 O was also reported by Oerter et al (2014).…”
Section: The Influence Of Calibration Methods On Dve-lssupporting
confidence: 67%
“…In this study, soil materials also received thermal treatment at 80°C. This produced samples with the same texture and carbon content, but increased SWR (i.e., increased CA; Gaj et al, 2019). Such conditions may also be found in natural soils, e.g., in the contact zone of wildfires.…”
Section: Introductionmentioning
confidence: 75%
“…To provide homogeneous samples to allow for repetitive tests, samples were air-dried, sieved < 2-mm and divided into two portions. One portion of the airdried materials was treated at 25°C in a climate-controlled chamber and the other portion was treated at 80°C for 24 hours in an oven to emulate a higher level of SWR in conjunction with stronger persistence of SWR (Gaj et al, 2019). The 25°Ctreated material served as reference.…”
Section: Soil Samples and Studied Areamentioning
confidence: 99%
“…This capillary fringe of effectively saturated soil water may increase mixing processes throughout the hillslope and negate any evaporative enriched shallow soil water as the quantity of water in the near surface is quantitatively smaller than in the subsurface. Gaj et al () showed that the degree of transport, mixing and fractionation of water stable isotopes within the unsaturated zone under drought is controlled by the composition of the biogeochemical interface, soil tension, and wettability. Especially the use of stable isotope signatures of soil water and water vapour at the dry end of the water retention curve (around wilting point) is largely unexplored, but nevertheless important, because these dry conditions occur preferentially at the shallow soil depths, where evaporation into the atmosphere occurs (Gaj & McDonnell, ).…”
Section: Discussionmentioning
confidence: 99%